LncRNA DLGAP1‐AS1 accelerates glioblastoma cell proliferation through targeting miR‐515‐5p/ROCK1/NFE2L1 axis and activating Wnt signaling pathway. Issue 10 (18th September 2021) - Wang, Zixuan; Han, Yipeng; Li, Qifeng; Wang, Baocheng; Ma, Jie
Abstract: Introduction: Glioblastoma (GBM), the primary malignant tumor in the central nervous system, features high aggressiveness and mortality. Long noncoding RNAs (lncRNAs) can exert the crucial function in regulating various human diseases, including GBM. However, the function and mechanism of lncRNA DLGAP1 antisense RNA 1 (DLGAP1‐AS1) in GBM remain still unknown. Methods: DLGAP1‐AS1 expression in GBM cells was detected by RT‐qPCR. Functional assays were conducted to determine GBM cell proliferation and apoptosis. RIP, RNA pull down, and luciferase reporter assay were applied for measuring the interplay of DLGAP1‐AS1 with other RNAs. Results: DLGAP1‐AS1 was distinctly upregulated in GBM cells. DLGAP1‐AS1 depletion inhibited cell proliferation, but induced apoptosis. MiR‐515‐5p could be sponged by DLGAP1‐AS1 in GBM cells and to repress cell proliferation in GBM. Further, Rho‐associated coiled‐coil containing protein kinase 1 (ROCK1) and Nuclear factor erythroid‐2 like 1 (NFE2L1) were confirmed as the target gene of miR‐515‐5p. Wnt signaling pathway could be activated by DLGAP1‐AS1 via regulating ROCK1 and NFE2L1 expression. Rescue assays proved that overexpression of both ROCK1 and NFE2L1 could totally reverse the inhibitory effect of silencing DLGAP1‐AS1 on GBM cell proliferation. Conclusion: LncRNA DLGAP1‐AS1 accelerated cell proliferation in GBM via targeting miR‐515‐5p/ROCK1/NFE2L1 axis and activating Wnt signaling pathway. Abstract : 1. DLGAP1‐AS1 is significantly upregulated in GBM cells and facilitates cell proliferation. 2. DLGAP1‐AS1 binds to miR‐515‐5p by acting as a ceRNA in GBM. 3. NFE2L1 and ROCK1 are targeted by miR‐515‐5p in GBM.